Protein concentrations of sweet soysauces from Rhizopus oryzae and R. oligosporus fermentation without moromi fermentation - TJAHJADI PURWOKO; NOOR SOESANTI HANDAJANI (Biodiversitas Journal of Biological Diversity, 2007)
Soy sauce was produce from soybean that fermented with koji/tempeh fungi and thenfermented under salt solution or moromi fermentation. The objectives of this experiment was to compare of protein (total and soluble) content of sweet soy sauce that produced from soybean fermented with Rhizopus oryzae and R. oligosporus without moromi fermentation to the sweet soysauce with moromi fermentation one. The total and soluble proteins of sweet soy sauces that produce from soybean without moromi fermentation were higher that sweet soy sauces that produce with moromi fermentation. Soluble protein of sweet soy sauce that produced from soybean fermented with R. oligosporus without moromi fermentation was 8.2% and meet to the highest quality of sweet soy sweet sauce based on Indonesia Industrial Standard. Soluble protein of sweet soy sauce that produced from soybean fermented with R. oryzae without moromi fermentation was 4.1% and meet to the medium quality of sweet soy sweet sauce based on Indonesia Industrial Standard.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: moromi fermentation, Rhizopus oligosporus, Rhizopus oryzae, soluble protein, sweet soy sauce